Mitigation of Damage in Contract Breach: Basis and Potential Scope in Ecuador - Ayala López, Doménica Lisseth (2025)
This study examines damage mitigation in contractual breaches, exploring its theoretical basis and potential scope in Ecuador. It analyzes its legal nature and role within contractual relationships, assessing whether it constitutes an expression of good faith, a creditor’s obligation, or a procedural burden affecting compensation claims. Its compatibility with fundamental principles such as restitutio in integrum and its impact on determining compensable damages are also evaluated. From a normative perspective, the study reviews its regulation in Ecuador, where its express recognition in the Commercial Code appears to grant creditors a faculty rather than impose a strict obligation. In the absence of relevant case law, its application is examined academically, emphasizing its impact on evidentiary matters. Accordingly, its rules, standards, and limitations are analyzed to prevent excessive burdens on the creditor. The methodology combines a literature review with a normative interpretation exercise, systematizing academic, doctrinal, and legal sources. Additionally, artificial intelligence was used  as a drafting support tool, ensuring coherence and accuracy through the author’s review.